Penıngkatan Hasıl Belajar Model Project Based Learnıng Berbasıs Lapbook Kelas III SDN 1 Semplo - Suweni; Dianasari; Prabawati Nurhabibah (Elementary Teacher Education Program, Majalengka University, 2023)
This research is based on a preliminary study obtained in the initial data on improving math learning outcomes which only reached 45%, so it is necessary to apply a project-based learning model based on lapbook media. This study aims to determine the improvement of student learning outcomes through a lapbook-based project-based learning model in third grade math lessons at SDN 1 Semplo. The type of research used is Classroom Action Research (PTK). The research subjects were third grade students of SD Negeri 1 Semplo with a total of 29 students. The data collection techniques used were observation, interviews, tests and documentation. The data analysis technique used was descriptive quantitative and qualitative. The project-based learning model which is a learning model that uses an activity, project as a medium that results in an increase in student learning outcomes, while the lapbook is a medium produced using project-based learning which can be a portfolio of student work and assignments. The increase in pre-cycle learning outcomes was 45% (13 students), increased in cycle I to 62% (18 students) and in cycle II increased to 86% (25 students). So, by applying the Lapbook-based Project Based Learning (PjBL) learning model can improve the learning outcomes of third grade Mathematics students of SDN 1 Semplo.